Budesonide foam for mild to moderate distal ulcerative colitis: A systematic review and meta‐analysis. Issue 3 (March 2017) - Zeng, Jian; Lv, Lin; Mei, Zhe‐Chuan
Abstract: Background and Aim: Budesonide is a second‐generation steroid with prominent topical effects and minimal systemic activity for patients with ulcerative colitis (UC). We perform a systematic review and meta‐analysis of randomized placebo‐controlled trials to assess the efficacy and safety of budesonide foam in mild‐to‐moderate distal UC. Methods: Comprehensive searches were performed to identify all eligible studies. Outcome measures were clinical remission, endoscopic improvement, elimination of rectal bleeding, and adverse events. The risk ratio (RR) with 95% confidence interval (CI) was estimated for each outcome. All statistical analyses were performed in STATA 12.0. Results: Three randomized placebo‐controlled trials recruiting 711 patients with mild‐to‐moderate distal UC were included in this study. No significant bias and heterogeneity was identified. Pooled analyses showed that budesonide foam was significantly superior to placebo for induction of clinical remission (RR = 1.83, 95%CI: 1.41, 2.37; P  < 0.001) and endoscopic improvement (RR = 1.44, 95%CI: 1.23, 1.68; P  < 0.001), and eliminating rectal bleeding at week 2 (RR = 2.00, 95%CI: 1.50, 2.66; P  < 0.001), week 4 (RR = 1.73, 95%CI: 1.42, 2.12; P  < 0.001), and week 6 (RR = 1.76, 95%CI: 1.45, 2.14; P  < 0.001). No statistically significant difference was observed in the incidence of treatment‐related adverse events and therapeutic discontinuation because of adverse events between budesonide foam and placebo. Conclusions: Budesonide foam is well tolerated and superior to placebo in inducing clinical remission and endoscopic improvement, and eliminating rectal bleeding for mild‐to‐moderate distal UC.